Inter-subjectivity and Domestication in the Making of a Global Region: Territorialization of Salmon in the Chilean Patagonia - Gustavo Blanco Wells; Alberto Arce; Eleanor Fisher (Íconos)
This article examines transformations in the Chilean Patagonia, a region that has become a world leader in Salmon production for global markets. Employing ethnographic methods, this study examines the possibilities of considering inter-subjectivities in the processes of conforming important regions in the global production of foods in contrast to some perspectives that emphasize inter-objectivity in analyzing human and non-human relations. In a complex and globalized world, assembly theory permits us to understand how forms of bio-power stimulate regional transformations that then generate new relationships between life, agency and nature. The analysis focuses on experiments, encounters and affects, decentering conventional perspectives about the domestication of species, regional development and food production. It opens a debate about the potentialities and limits of non-lineal interpretations of reality.